1966
DOI: 10.1128/jb.91.6.2263-2269.1966
|View full text |Cite
|
Sign up to set email alerts
|

Altered End-Product Patterns and Catabolite Repression in Escherichia coli

Abstract: End products formed during growth of Escherichia coli ML30 on glucose were examined under various conditions known to promote or prevent catabolite repression of the inducible js-galactosidase system in this organism. Cultures were grown under these conditions in the presence of C14-glucose or C14pyruvate. The products formed were assayed isotopically after separation on columns of silicic acid. Under conditions known to promote catabolite repression, glucose was degraded primarily to acetate and CO2. When rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…Current models of catabolite repression postulate the activation by a catabolite co-repressor of a genetic apo-repressor which can turn off transscription of the lac operon through a specific operator gene. The co-repressor may be a carbon catabolite (25, 28) or an energy-rich intermediate (8,35,36). In a carbon-limited continuous culture, the level of co-repressors increases as the cells grow faster, resulting in stronger repression and diminishing enzyme level.…”
Section: @-Galactosidase Synthesis and Lactose Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Current models of catabolite repression postulate the activation by a catabolite co-repressor of a genetic apo-repressor which can turn off transscription of the lac operon through a specific operator gene. The co-repressor may be a carbon catabolite (25, 28) or an energy-rich intermediate (8,35,36). In a carbon-limited continuous culture, the level of co-repressors increases as the cells grow faster, resulting in stronger repression and diminishing enzyme level.…”
Section: @-Galactosidase Synthesis and Lactose Utilizationmentioning
confidence: 99%
“…If the regulatory controls on catabolism become overloaded, i.e., unable to reduce the catabolic capacity of the cell to match the biosynthetic capacity, metabolic intermediates accumulate within the cell and eventually spill out into the medium. Excretion of gluconic acid, 2-ketogluconic acid, acetate, pyruvate, and other catabolites by cells growing under fully aerobic conditions has been amply documented (8,27,32). Excretion of intermediate catabolites has been recently demonstrated in carbon-limited continuous cultures fed mixed substrates (S. K. Chian, Ph.D. Thesis, Massachusetts Institute of Technology, Cambridge, 1967; R. I. Mateles and S. K. Chian, submitted for publica-lion).…”
Section: @-Galactosidase Synthesis and Lactose Utilizationmentioning
confidence: 99%
“…Growth was measured photometrically using a Klett meter. The samples were then transferred to centrifuge tubes containing 5.0 ml of a cold carrier solution (Dobrogosz 1966) and centrifuged for 10 min at 27,000 g. The supernatant was decanted into test tubes, and stored at 4°C before analysis.…”
Section: Determination Of Glycolytic End-productsmentioning
confidence: 99%
“…The glycolytic end-products of the samples were separated using a slight modification of the liquid chromatographic technique of Dobrogosz (1966). A 9.0 mm ID column was employed.…”
Section: Determination Of Glycolytic End-productsmentioning
confidence: 99%
“…7) In the absence of oxygen and exogenous electron acceptors, the facultative anaerobes Escherichia coli and Corynebacterium glutamicum have been shown to produce succinate from sugars via the reductive TCA cycle. [8][9][10][11] We previously demonstrated that the sucE1 gene encodes a succinate exporter crucial for the production of succinate in C. glutamicum under anaerobic conditions. 12,13) In addition, of the anaerobic succinate transporters in E. coli, only the dicarboxylate uptake (Dcu) carriers DcuA-C have been characterized thus far.…”
mentioning
confidence: 99%